Management challenges in monophasic synovial sarcoma of distal femur with lung metastasis: to amputate or limb salvage surgery - Rubenandran, Ramachandran; M., Asyraf; D., Suryasmi; Chye, P. C.; Rampal, S.; Raghuraman, S. F. (Manipal Alumni Association Malaysia, 2020)
Synovial sarcoma is one of the commonest malignant soft tissue sarcomas with poor prognosis, especially when detected in late stages. It has a wide spectrum of biologic behavior, a high degree of local invasiveness and capability to spread trans compartment. There appears to be a lack in the reporting of these tumours locally as the challenges of diagnosis and management are often demanded at advance stages. We present a case of synovial sarcoma in an adolescent who presented very late with a huge lesion over right thigh with metastasis to the lung. This report highlights the diagnostic challenges which directly affect the type of surgical intervention and physical outcomes of patient.